2004
DOI: 10.1139/f04-208
|View full text |Cite
|
Sign up to set email alerts
|

Temporal synchrony and variation in abundance of Atlantic salmon (Salmo salar) in two subarctic Barents Sea rivers: influence of oceanic conditions

Abstract: Long-term variation in Atlantic salmon (Salmo salar) stocks was analyzed in two Barents Sea rivers, the Teno and Näätämöjoki, that represent the northernmost distribution area of the species. In contrast to most of the North Atlantic area, these rivers are among a group of northern salmon rivers that, despite wide annual variation in catches, demonstrate no consistent trend for declining abundance. Variations in abundance were generally synchronous for the total catch and numbers of 1-sea-winter (1SW) and 2SW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 24 publications
(36 reference statements)
3
37
0
Order By: Relevance
“…Factors common to all stocks during the feeding migration include changes in the sea environment, such as the sea surface temperature, conditions in the feeding area, such as the availability of food, and the offshore and coastal fishery. This reasoning has proved correct in several previous studies related to salmon abundance, growth, and migration distance, in which synchronous trends have been related to common environmental factors [6,13,62,63]. The decrease in the proportion of old males has also been observed previous studies , as Järvi [64] reported approximately 11% of the spawners to be 4-6 SW salmon in the 1930s and 1940s, but an analysis sixty years later reported only 0.5-2% of salmon of that age [15].…”
Section: Spawning Age Variation Caused By the Natural Environmentmentioning
confidence: 64%
See 1 more Smart Citation
“…Factors common to all stocks during the feeding migration include changes in the sea environment, such as the sea surface temperature, conditions in the feeding area, such as the availability of food, and the offshore and coastal fishery. This reasoning has proved correct in several previous studies related to salmon abundance, growth, and migration distance, in which synchronous trends have been related to common environmental factors [6,13,62,63]. The decrease in the proportion of old males has also been observed previous studies , as Järvi [64] reported approximately 11% of the spawners to be 4-6 SW salmon in the 1930s and 1940s, but an analysis sixty years later reported only 0.5-2% of salmon of that age [15].…”
Section: Spawning Age Variation Caused By the Natural Environmentmentioning
confidence: 64%
“…The spawning age of Atlantic salmon varies from one to five years, calculated as the number of winters spent in the marine feeding areas after their two to five freshwater years in the river [11,12]. Occasionally, salmon are able to recover from their first spawning and return to the sea, and even spawn for a second time [5,13,14], but in the Baltic Sea the proportion of such fish is currently only a few percent [15]. As a nearly semelparous fish, the final body size of the Atlantic salmon depends on its age at maturity.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Niemel ä et al (2004) found no correlation between the NAO and salmon catches in the rivers Teno and Naatamojoki (northern Finland), the stocks of which migrate to the Barents Sea and show large natural fl uctuations. Those catch time series date from the 1970s and are especially important because they run counter to the general pattern of recent stocks declines of Atlantic salmon (Niemel ä et al 2004(Niemel ä et al , 2005. Juvenile abundances increased over the period 1977 -2003 and strong smolt years were refl ected positively in subsequent returns of spawning adults, perhaps because of warmer oceanic conditions (Niemel ä et al 2004 ).…”
Section: Amo Departurementioning
confidence: 99%
“…The size of the salmon spawning run in rivers may vary largely among years, both in terms of numbers and proportion of the different sea-year classes (e.g. Niemelä et al, 2004). This temporal variation is due to variation in freshwater smolt production (e.g.…”
Section: Upper Sectionmentioning
confidence: 99%
“…Jonsson et al, 1998), variation in ocean climate (e.g. Jonsson & Jonsson, 2004a, b;Niemelä et al, 2004) and management measures affecting marine fisheries (e.g. Jensen et al, 1999).…”
Section: Upper Sectionmentioning
confidence: 99%